Development of methodology for polyamine analysis and its application to heavy metal-induced stress in apple plants - Wehr, J. Bernhard(Johannes Bernhard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1994.